Obstetric Outcome of Teenage Pregnancy - Kayastha, S; Pradhan, A (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To assess the prevalence of teenage pregnancies and to compare the obstetric performance of teenage pregnant woman with that of adult pregnant woman. Methods: A prospective study was conducted in Nepal Medical College Teaching Hospital from August, 2010 to February, 2012 (one and half year duration). All the teenage pregnancies were included and outcomes were compared with adult (20-24 years) pregnancies, selected randomly who had delivered during the same period of time. The patient characteristics (age, gravidity, parity, gestation age) and obstetric outcome (medical and obstetrical complications, mode of delivery, complications during delivery, fetal outcome, birth weight) were compared between the two groups. Statistical analysis was preformed using PHSTATZ and Z test for proportion. Results: There were total 2708 deliveries during the study period, out of which teenage pregnancy was 264 (9.7%). There were 69(26.1%0) teenage mothers of age 16 to 17 years and 195(73.9%) of age group 18 to 19 years. As expected, maximum patients in the test group i.e. teenagers were primigravida as compared to control group. (90.1% vs. 68.5%). As for mode of delivery, normal delivery in test and control was 82.9% vs 81.1% (p=0.56) and rate of cesarean delivery was similar 10.2% and 10.7%, (p=0.84) in both the groups. The incidence of instrumental delivery was more in control group although it was not statistically significant( 0.7% vs 2.2%, p=0.16). Preterm delivery was 3.0% in teenage as compared to control which is 2.2%. The percentage of intrauterine fetal death was 0.7% vs 0% in test and control group (p=0.15). Proportion of low birth weight babies in test and control group was 7.2% vs 5.9% (p=0.55). Similarly pregnancy related complications were also compared in teenage and control groups. It was found that postpartum hemorrhage occurred more in teenage pregnancy 1.8% vs 0.7% (p=0.84) but statistically not significant. Incidence of hypertensive disorders was 6.4% and 5.6% (p=0.66) in test and control group. Proportion of babies with intrauterine growth restriction was 3.0% in test and 1.1% (p=0.009) in control, the only parameter that is statistically significant. Fetal congenital anomaly was 0.7% vs 0.4% (p=0.54) Conclusions: Teenage pregnancy can have an equally good outcome if we give good obstetric care and encourage institutional delivery. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11139 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 29-32